Association between the IL-10 and IL-6 polymorphisms and brucellosis susceptibility: a meta-analysis - Xiaochun Jin; Yueyuan Wu; Shuzhou Yin; Xu Chen; Youtao Zhang (BMC, 2020)
Abstract Background Brucellosis is a quite normal zoonotic infection, which is caused by immediate contact with animals infected with Brucella or its products. IL-10 (− 1082 G/A, − 819 C/T, − 592C/A) and IL-6 -174 G/C polymorphisms have a great relationship with IL-10 and IL-6 production, which brings about Brucellosis pathogenesis and development. So far, the results of published literatures were controversial. Now, we perform a meta-analysis in different ethnic populations to get a more precise estimate of above polymorphisms with Brucellosis susceptibility. Methods Both OR and corresponding 95%CI were enrolled to make an assessment of the association strength through extracting genotyping frequency of cases and controls. The χ2-test based Q-statistic and I2 statistics were applied. If there was no evident heterogeneity, the fixed-effects model would be applied. If not, the random-effects model would be used. Results The significant associations were only found in Asian population of − 819 loci under three genetic models as follows: (Allele model: OR = 0.60, 95%CI = 0.44-0.82, P = 0.001), (homozygote comparison: OR = 0.24, 95%CI = 0.09-0.62, P = 0.003), (recessive genetic model: OR = 0.22, 95%CI = 0.05-0.91, P = 0.036). Conclusion In conclusion, IL-10 − 819 loci polymorphism contributes no risk to Caucasian population but may be associated with decreased risk in Asian population. And IL-10 -1082 G/A, 592 loci and IL-6 -174 G/C polymorphism are not associated with Brucellosis risk.